1999
DOI: 10.1111/1467-8489.00077
|View full text |Cite
|
Sign up to set email alerts
|

Commodity futures markets: a survey

Abstract: This review article describes the main contributions in the literature on commodity futures markets. It is argued that modern studies have focused primarily on technical questions, with insu¤cient economic content. More research needs to be directed towards understanding fundamental economic issues such as why so few farmers hedge, the impacts of government farm programs on commodity futures, and the market impacts of commodity pools. The literature has failed to explain the prevalence of inverted markets in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 143 publications
(165 reference statements)
3
43
0
2
Order By: Relevance
“…Moreover, this confirms the general findings of empirical studies on commodity futures markets (see Cox 1976or Carter 1999, for a review), which show that the forward price conveys some information that increases the predictability of spot prices. However, we should note that primeur sales do not have all the typical features of forward contracts, since there is no guarantee on the quality of the wine that is going to be delivered.…”
supporting
confidence: 87%
“…Moreover, this confirms the general findings of empirical studies on commodity futures markets (see Cox 1976or Carter 1999, for a review), which show that the forward price conveys some information that increases the predictability of spot prices. However, we should note that primeur sales do not have all the typical features of forward contracts, since there is no guarantee on the quality of the wine that is going to be delivered.…”
supporting
confidence: 87%
“…Reviews of the literature are provided by Carter (1999), Kamara (1982), and Gray and Rutledge (1971), among others. 5 Momentum in commodity futures has been documented by Pirrong (2005), Erb and Harvey (2006), Miffre and Rallis (2007), and Shen, Szakmary, and Sharma (2007).…”
Section: Momentum In Commodity Futures Excess Returnsmentioning
confidence: 99%
“…Carter (1999) showed that most of the literature concerning hedge in the past fifty years investigates the optimal hedge ratio.…”
Section: Literature Reviewmentioning
confidence: 99%